Fetomaternal Outcomes in Pregnant Women having Epilepsy at Nishter Hospital, Multan - Nabeela Atta; Muhammad Ramzan; Rabia Bhatti; Atif Maqsood; Sadaf-Un-Nisa; Bilal Rafique Malik (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Epilepsy is a common neurological disorder characterized by recurrent seizures, About 40% females may develop the disorder in reproductive age, leading to episodes of epilepsy in pregnancy and cause severe consequences. Objective: To determine fetomaternal outcomes in pregnant women having epilepsy at a tertiary care Nishter hospital MULTAN Study Design: Retrospective study Study Place and duration: Department of Obstetrics & Gynecology, in collaboration with Neurology Department, Nishtar Hospital Multan from 1st Jan 2021 to 31st Dec 2021 Patients and Methods: A total of 100 pregnant women with epilepsy were included in the study. The patients with epilepsy were recruited for pregnancy outcomes till delivery to determine outcomes. All the relevant information was noted in proforma while analysed in SPSS. Results: Age range in this study was from 20 to 40 years with mean age of 28.951+2.69 years. Majority of the patients were of 20-30 age group i.e. 78%. C-section was done in 24.4% patients, low birth weight was observed in 19.5% patients, small for gestational age 9.8% and preterm delivery was 19.5%. Conclusion: Our study concluded that pregnancies with epilepsy, even in cases with multidisciplinary care and no other risk factors, are still significantly associated with higher adverse outcomes. Key words: Epilepsy, Adverse feto-maternal outcomes, cesarean section, low birth weight, preterm delivery